3D and transient numerical modelling of door opening and closing processes and its influence on thermal performance of cold rooms. (25th February 2017) - Carneiro, Rui; Gaspar, P.D.; Silva, P.D.
Highlights: A 3D CFD modelling of opening/closing cycle of cold room's doors is developed. The CFD simulation uses the tracer gas concentration decay experimental technique. Air infiltration rate through sliding door is 20% lower than through a hinged one. Air temperature inside cold room with sliding door is 17% lower than with hinged one. The developed model extends the analytical results for door opening/closing periods. Abstract: This paper presents the comparison of three-dimensional and transient CFD modelling of the opening and closing processes of hinged and sliding doors and its influence on the thermal performance of cold rooms. A species transport model is used to model a tracer gas. The air infiltration through the door opening is determined by the tracer gas concentration decay technique. The prediction of air temperature and velocity fields in the cold room as function of external air temperature allows quantifying the increase of the air infiltration rate and consequently of the average air temperature inside the cold room. When the hinged door is used, the formation of vortices during the opening movement promotes a larger and faster thermal interaction between the two contiguous air masses. The air infiltration during the sliding door opening/closing is 20% lower than for a hinged door. Consequently, the average air temperature inside the cold room is 17% lower. The air infiltration rate was numerically predicted and compared with analytical models' results. The numerical model predicts closely the air infiltration rate for each door type. Moreover, the transient CFD modelling extends the results of the analytical models allowing the analysis of the influence of door opening and closing processes on the air temperature and velocity fields.